The power of collaboration : powerful insights from Silicon Valley to successfully grow groups, strengthen alliances, and boost team potential - Spitzer, Thea Singer (Business professional collection, 2018)
Showing how any company, anywhere, can adapt to achieve its goals, this cutting-edge book combines the author's longstanding expertise with innovative thinking, research, and focused interviews to provide a practical framework for the next epoch of collaboration. --